2021
DOI: 10.32920/ryerson.14654391.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energy modelling and field testing of natural gas absorption heat pump system in cold climate - Canada

Abstract: The feasibility of a Natural Gas Absorption Heat Pump (GAHP) was investigated through the use of a technology screening tool developed in Excel and TRNSYS simulations that used experimentally evaluated performance curves using 50% propylene glycol (PG)/water solution. The Excel tool was used for cost and greenhouse gas (GHG) reductions analysis and indicated that the GAHP was cost effective compared to an Air-Source Heat Pump (ASHP) in locations where the primary heating fuel was natural gas and had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study by the Independent Electricity System Operator (IESO) showed that the price of natural gas has to increase by at least 50% for electrical heat pumps to be a viable replacement for natural gas-fired furnaces (IESO, 2017a). In the prevailing circumstances the adoption of alternative heating equipment such as the natural gas-fired heat pump (GHP) can emerge as a viable option for replacement of conventional fossil fuel-fired heating equipment when considering savings in energy and operational cost, and reduction in GHG emissions (Ethirveerasingham, 2018).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…A study by the Independent Electricity System Operator (IESO) showed that the price of natural gas has to increase by at least 50% for electrical heat pumps to be a viable replacement for natural gas-fired furnaces (IESO, 2017a). In the prevailing circumstances the adoption of alternative heating equipment such as the natural gas-fired heat pump (GHP) can emerge as a viable option for replacement of conventional fossil fuel-fired heating equipment when considering savings in energy and operational cost, and reduction in GHG emissions (Ethirveerasingham, 2018).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%